Richard Wright's art of tragedy - Joyce, Joyce Ann, 1949- (Iowa City : University of Iowa Press, 1986)
Annotation. First published (hardcover) in 1986. Joyce focuses specially on the stylistic characteristics of Wright's most successful novel to show how his language merges with his subject matter to illuminate Native son as a tragedy. Annotation copyrighted by Book News, Inc., Portland, OR.
The Critical Background and a New Perspective -- Setting and Structure: The Cosmology of Bigger's World -- Characterization and Point of View: The Tragic Hero -- Technique: The Figurative Web -- The Unity of Book 3: A Synthesis of the Theme.
Includes bibliographical references (pages 121-125) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Wright, Richard, -- 1908-1960.; Native son (Wright, Richard); African American men in literature; Tragic, The, in literature; Hommes noirs américains dans la littérature.; Tragique dans la littérature.; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM / General; African American men in literature; Tragic, The, in literature; Native son (Wright)